Third-Party Logistics Practices in E-commerce of Nepal: A Narrative Study of the Supply Chain Professionals - Praveen Chaudhary; Pratibha Kiran Niroula (Research Synergy Press, 2023)
In recent years, the rapid growth of e-commerce has revolutionized the way businesses operate and consumers engage in commercial activities. This transformative shift has brought about unprecedented convenience and accessibility, enabling global consumers to shop for products and services from the comfort of their homes, including in Nepal. Simultaneously, the demand for the intricate web of operations behind these transactions (logistics management) has become paramount. And, in the realm of logistics, the notion of outsourcing by means, of third-party logistics (3PL) emerges as a pivotal strategy. Subsequently, this study embodies a pragmatic perspective through the qualitative study using the narrative approach thus by unstructured interviews with the select information-rich supply-chain service professionals in e-commerce companies employing the 3PL practices in their logistical fulfilments. The study illuminates on the circuitous reciprocity between 3PL strategies and the distinctive features of Nepal's e-commerce landscape filled with infrastructural challenges and urban- rural divide that co-exist with opportunities. The findings revealed that the core focus, reach, digitalization, financial viability, product safety, and logistical efficiency concerns influence the 3PL outsourcings. It also delves through the prevalent practices, challenges, and opportunities, and also optimization measures from the perspective of supply chain professionals, shedding light on the path forward for optimizing logistics for e- commerce, emphasizing the coherent need to incorporate the digital shift, customer-centricity, continual learnings and financial prudency, thus holds a significant importance.